PENGEMBANGAN ENSIKLOPEDIA ATLETIK NOMOR LEMPAR PADA KELAS V UPTD SDN KRATON 1 BANGKALAN - Safaah, Saniyatus; Ana Naimatul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop an encyclopedia-based teaching material on athletics throwing events for fifth-grade students at UPTD SDN Kraton 1 Bangkalan. The development was motivated by the limited availability of Physical Education, Sports, and Health (PJOK) teaching materials, which caused students to experience difficulties in understanding the subject matter and reduced their participation during the learning process. Therefore, an innovative teaching material that is attractive, systematic, and easy to understand was needed to support learning activities. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects involved material experts, product design experts, instructional design experts, teachers, and fifth-grade students. Data were collected through validation questionnaires, observation sheets, learning outcome tests, readability questionnaires, and teacher and student response questionnaires. The results indicated that the developed athletics throwing-event encyclopedia met the criteria of validity, effectiveness, attractiveness, and practicality. The validity scores were 95% from material experts, 89.58% from product design experts, and 90% from instructional design experts, all categorized as very valid. The effectiveness of the product was demonstrated by student activity reaching 91.33%, teacher activity reaching 100%, and classical learning mastery reaching 100%. Furthermore, the attractiveness level reached 95% based on teacher responses and 91.25% based on student responses. The practicality level was 92.5% based on student responses and 100% based on teacher responses. Therefore, the athletics throwing-event encyclopedia is feasible and effective to be used as a teaching material in PJOK learning at the elementary school level.